2018
DOI: 10.1055/s-0038-1673624
|View full text |Cite
|
Sign up to set email alerts
|

Severe Troponin I Elevation and Myocardial Dysfunction in a Child with Scorpion Sting

Abstract: Background Scorpion sting is a common medical problem and major cause of mortality and morbidity in many countries. The symptoms of envenomation are more severe in the pediatric population. The clinical manifestations of scorpion envenomation appear by activation of sympathetic and parasympathetic nervous system. Envenomation can cause multiorgan dysfunction and death. Case Presentation and Findings In this case report, we present a pediatric patient from Adana, Southeast Anatolia, with severe scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
9
0
4
Order By: Relevance
“…Ventricular tachycardia was another important finding [ 71 , 75 , 76 , 84 ]. Laboratory findings associated with myocarditis were raised levels of cardiac troponin T [ 49 , 57 , 61 , 64 , 70 , 72 , 75 , 87 ], troponin I [ 34 , 41 , 42 , 45 , 46 , 49 , 58 , 60 , 65 , 66 , 74 , 76 , 78 , 79 , 81 , 82 , 84 86 , 88 , 91 , 92 ], unspecified-type troponin [ 63 , 67 , 80 , 82 ], CK-MB [ 14 , 18 , 34 , 37 , 40 , 45 , 46 , 49 , 52 , 57 , 59 , 62 , 66 , 68 , 70 , 74 76 , <...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ventricular tachycardia was another important finding [ 71 , 75 , 76 , 84 ]. Laboratory findings associated with myocarditis were raised levels of cardiac troponin T [ 49 , 57 , 61 , 64 , 70 , 72 , 75 , 87 ], troponin I [ 34 , 41 , 42 , 45 , 46 , 49 , 58 , 60 , 65 , 66 , 74 , 76 , 78 , 79 , 81 , 82 , 84 86 , 88 , 91 , 92 ], unspecified-type troponin [ 63 , 67 , 80 , 82 ], CK-MB [ 14 , 18 , 34 , 37 , 40 , 45 , 46 , 49 , 52 , 57 , 59 , 62 , 66 , 68 , 70 , 74 76 , <...…”
Section: Resultsmentioning
confidence: 99%
“…One study reported hemoglobin and plasma protein to be higher in patients with pulmonary edema [ 39 ]. Elevated serum glucose [ 26 , 34 , 37 , 38 , 41 , 47 , 61 , 62 , 65 , 66 , 72 , 73 , 84 , 85 , 87 ], amylase [ 37 , 38 , 44 , 47 , 62 , 81 , 84 , 87 ], creatinine phosphokinase [ 18 , 26 , 38 , 44 , 47 , 51 , 55 , 59 , 62 , 69 , 72 , 74 , 76 , 78 , 90 ], lactate dehydrogenase [ 55 , 78 , 81 , 89 , 90 ], alanine transaminase [ 73 , 83 , 86 , 87 ], aspartate transaminase [ 26 , 44 , 62 , 64 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations